Pengetahuan, sikap, perilaku, dan asupan gizi berdasarkan status hidrasi ibu hamil - Erry Yudhya Mulyani; Idrus Jus'at; Dudung Angkasa; Dwikani Oklita Anggiruling; Enrico Stanin (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
Maternal nutritional knowledge, attitude, behavior, and intake based on hydration statusBackground: Based on past studies, 49% of pregnant women had low knowledge of nutrition and hydration. Nutritional knowledge, attitudes, and behavior are positively correlated to nutritional intake, malnutrition and dehydration may disturb maternal health and pregnancy outcome.Objectives: To analyze maternal nutritional knowledge, attitudes, behavior, and nutritional intake based on the hydration status.Methods: This cross-sectional study was conducted at Puskesmas Kebon Jeruk District, West Jakarta using a purposive sampling method. Subjects were 50 pregnant women who came to check their pregnancies. Subject’s characteristics, nutritional knowledge, attitudes, and behavior are collected with a questionnaire, nutritional intake with 1x24 hours recall. Hemoglobin (Hb) level is determined with Haemometer, urine specific gravity with Urinometer, and urine color with PURI card.Results: Subjects had an average age of 29.0±5.7 years, gestational age 21.3±11.3 weeks, weight 62.7±9 kg, height 158.1±4.1 cm, upper arm circumference 32.4±29.5 cm, Hb level 12.2±0.9 g/dL, urine color score 4±0.9, and urine specific gravity 1016±5.4. Based on urine specific gravity, 56% of the pregnant women were euhydrated and 44% were dehydrated. Based on the hydration status there were no differences in knowledge, attitudes, behavior, and macronutrient intake (p≥0.05), except for the fluid intake (p<0.05).Conclusions: Although the knowledge, attitudes, and nutritional behavior of pregnant women were not poor, optimization of the fluid consumption to 3L/day, and diversified food consumption is needed. Further research on external factors that can affect the nutritional status and hydration of pregnant women is recommended.